VISUALISASI PEPATAH-PETITIH MINANGKABAU Dalam SENI LUKIS SURREALIS - IRWAN, Drs. Erfahmi,M.Sn, Drs. Ady Rosa,M.Sn (Serupa The Journal of Art Education, 2014)
Authors raise the culture of pepatah-petitih Minangkabau previously in the form of literature, from the words that exist in the pepatah-petitih writer to visualize in the form of paintings by surrealist style. Aiming visualize pepatah-petitih Minangkabau socio cultural in surrealist paintings. Displays a visual form of the words that exist in the previous pepatah-petitih in the form of verbal language. Sources of ideas based on interest author with existing words in the pepatah-petitih that in just a few words but the meaning and philosophy in the Minangkabau and the younger generation no longer familiar with the culture and prefer to use foreign cultures. The author raised the pepatah-petitih Minangkabau with different packaging in the form of surrealist painting. Of a long process of creating visualizations proverbial ten-born pepatah-petitih Minangkabau implies, advice and profound philosophy.Keywords : Visualisasi, Pepatah-Petitih Minangkabau, Seni Lukis Surrealis.